STANDARISASI KODE ETIK PROFESI BIMBINGAN DAN KONSELING - Nuzliah Nuzliah; Irman Siswanto (Fakultas Tarbiyah dan Keguruan UIN Ar-Raniry, 2019)
The professional code of ethics is a reference for individual behavior or a suit which is deemed necessary for professional activity actors to follow. Professionals have specific skills and a professional code of ethics is created to govern how this knowledge and expertise is used. In general, there are three functions of the code of ethics, namely: (1) Providing guidelines for every member of the profession regarding the principles of professionalism, (2) As a means of social control for the community over the profession concerned, (3) Preventing interference from parties outside professional organizations regarding ethical relations In the event of a violation of the Guidance and Counseling Professional code of ethics, the following sanctions will be given to him: Giving verbal and written warnings, Giving a strong written warning, Revoking ABKIN membership, Revoking the license, If it is related to legal / criminal issues then it will be handed over to the authorities